INFLUENCE OF HOME TO SCHOOL COMMUNICATION ON ACADEMIC ACHIEVEMENT OF STANDARD EIGHT PUPILS IN PUBLIC PRIMARY SCHOOLS IN KISUMU WEST SUB -COUNTY, KENYA - Juma, Lucy Stella A. (African Journal of Education and Practice, 2021)
Purpose: The purpose of the study was to establish the influence of home to school communication on academic achievement of pupils in public primary schools. Methodology: The research design used was sequential explanatory research design, which combined both qualitative and quantitative models of research so that evidence may be mixed and knowledge increased in a more meaningful manner. The study population consisted of 1210 standard eight pupils, 300 standard eight teachers, 1210 standard eight parents and 75 Head teachers drawn from 75 public primary schools in Kisumu West Sub-County, Kisumu, Kenya. Stratified random sampling technique was employed for selecting 23 public primary schools and simple random sampling used in each stratum to select the pupils. Purposive sampling technique was done to select standard eight parents, and head teachers. The researcher would collect data using questionnaires and interview schedule, focus group discussions guide and document analysis. Quantitative data was analyzed through descriptive and results presented in the form of tables, frequencies, Percentages, and accumulative percentages and on the other hand qualitative data generated from open ended questions were organized, categorized and presented in narratives. Findings: The study established that home to school communication affected pupils' academic achievement. Unique contribution to theory, practice and policy: The recommendations of the study were that there should be regular academic clinics and pupils progress follows up to help enhance achievement amongst the learners. The ecological system theory of development by (Bronfenbrenner 1969) outlined the influence of parent involvement at schools and the other surrounding influences on a child's development and academic achievement which the ministry could borrow to enhance academic achievement